An Opportunity to Engage Obstetrics and Gynecology Patients Through Shared Visit Notes. Issue 1 (July 2019) - Herlihy, Mary; Harcourt, Kendall; Fossa, Alan; Folcarelli, Patricia; Golen, Toni; Bell, Sigall K.
Abstract : OBJECTIVE: To assess obstetrics and gynecology patients' interest in reading their ambulatory visit notes, identification of documentation errors, and perceptions of sensitive language through a quality improvement (QI) initiative. METHODS: Beginning April 2016, as part of a QI project all obstetrics and gynecology patients (except family planning) were invited to read their ambulatory visit notes and provide feedback using a patient reporting tool codeveloped with patients. Two physicians with safety expertise reviewed all patient-reported errors over the first 16 months. RESULTS: Among obstetrics and gynecology patients with an active portal account and an available note, 6, 594 of 9, 550 (69%) read at least one note. Two hundred twelve (3.2%) patients used the electronic reporting tool, submitting a total of 232 reports, in a "natural" environment with no advertisement, incentives, or clinician encouragement. In total, 94% felt they understood the notes, 95% understood the next steps in the care plan, and 92% felt the notes accurately described their visit. Of all reports, 27% of patients identified inaccuracies in the notes, including descriptions of symptoms (29%); family history (21%); medications (15%); health problems (15%); social history and physical examination, including elements that were reportedly documented but not performed (each 11%). Patients rated inaccuracies as important in 58% of reports, and, on clinician review, 75% of patient-reported mistakes had the potential to affect care. Among all reports, 7% of patients indicated bothersome words. More than half (56%) of patients included voluntary positive feedback such as appreciation for the health care provider, reassurance from notes, greater visit recall and care plan adherence, and positive effects on the patient–doctor relationship. DISCUSSION: Obstetrics and gynecology patients are interested in reading notes, which can promote engagement and safety. Few patients provided feedback, but those who did identified documentation inaccuracies in about one quarter of reports; the majority were relevant to care. Greater outreach and patient encouragement are needed to further engage patients in safety. Abstract : When obstetrics and gynecology patients access their ambulatory visit notes, they read the notes, describe engagement benefits, and can identify care-relevant errors.